An Overview of the Current State of Pediatric Scoliosis Management - Rüwald, Julian M.; Eymael, Robin L.; Upenieks, Janis; Zhang, Li; Jacobs, Cornelius; Pflugmacher, Robert; Schildberg, Frank A. (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Historically pediatric scoliosis represents a condition deeply rooted within the origins of orthopedic surgery. Today only a few subspecialized surgeons treat pediatric scoliosis patients. In severe cases surgery can hold progression of and correct pathologic spinal curvature. The goal of this article is to provide an overview of the current state of pediatric scoliosis management. It aims to increase the attention of general physicians and orthopedic surgeons to a niched but rather frequently encountered pediatric pathology to facilitate early recognition and diagnosis. A thorough research of literature was conducted to summarize the different scoliosis types, their etiology and presentation. Classification, normal human growth phases and curve progression risk have been further elaborated. Finally, current treatment options with their benefits, shortcomings and complications were laid out and discussed. Among the etiological groups a focus was put on idiopathic scoliosis, in particular adolescent idiopathic scoliosis as the most frequently encountered subtype.
Keywords: pediatric scoliosis management; adolescent idiopathic scoliosis; current review